Ghost knight - Funke, Cornelia Caroline; Offermann, Andrea; Latsch, Oliver (New York : Little, Brown, 2012)
Eleven-year-old Jon Whitcroft and new friend Ella summon the ghost of Sir William Longspee, who may be able to protect Jon from a group of ghosts that threatens him harm from the day he arrives at Salisbury Cathedral's boarding school. Includes historical notes.
Relocating to a new boarding school only to be confronted by a group of vengeful ghosts, Jon and his friend, Ella, team up to uncover a centuries-old murder and summon the ghost of a medieval knight who they are not sure can be trusted.
Keywords: Salisbury Cathedral -- Fiction; Salisbury Cathedral -- Fiction; Ghosts -- Fiction; Knights and knighthood -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Knights and knighthood -- Fiction; Private schools -- Fiction; Salisbury (England) -- Fiction; England -- Fiction; Salisbury (England) -- Fiction; School stories; Ghost stories